From Marginal to Mainstream: An Argument for Locating Education Development in the Academic Department - Duthie, Shawn Robert; Freeman, Laura (South African Journal of Higher Education, 2016)
This paper contends that core responsibility, formation and execution of education development (ED) initiatives should occur within the academic department. For too long, ED has been handed off to peripheral bodies within South African universities. These programmes are limited in their reach, relevance and usefulness to students. Through a case study of ED in the Department of Political Studies at the University of Cape Town, we argue that ED within the academic discipline has three major benefits: (i) initiatives can develop based on effective identification of student need, (ii) ED can be normalised and its stigma can be reduced, and (iii) ED becomes discipline-specific and properly contextualised to student learning.